2019
DOI: 10.1111/edt.12501
|View full text |Cite
|
Sign up to set email alerts
|

In vitroevaluation of plants as storage media for avulsed teeth: A systematic review

Abstract: Background/AimsDental avulsion is defined as the complete displacement of a tooth from its socket owing to trauma. The treatment outcome depends on storage of the avulsed teeth in media capable of maintaining the viability of periodontal ligament cells, when immediate replantation is not possible. To maintain the viability of periodontal ligament cells, plants can be used as a storage medium because of their pharmacological and phytotherapic properties. The aim of this study was to evaluate the effect of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 55 publications
0
20
0
2
Order By: Relevance
“…Forty‐four SRs had been published in last six years (2015‐2020) 18‐78 . Twenty‐eight of the SRs had been published in Dental Traumatology, 16,17,20‐27,29,30,36,39‐41,44,45,59,60,67,69,71,74,75,77,78 and five were from the Cochrane database 38,46,50,53,70 . The remaining SRs were spread across journals in general dentistry, sports medicine, orthodontics, special care dentistry, endodontics, maxillofacial radiology, oral and maxillofacial surgery, pediatric dentistry, oral sciences, periodontology, community dentistry, epidemiology, dental hygiene, education sciences, and restorative dentistry (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐four SRs had been published in last six years (2015‐2020) 18‐78 . Twenty‐eight of the SRs had been published in Dental Traumatology, 16,17,20‐27,29,30,36,39‐41,44,45,59,60,67,69,71,74,75,77,78 and five were from the Cochrane database 38,46,50,53,70 . The remaining SRs were spread across journals in general dentistry, sports medicine, orthodontics, special care dentistry, endodontics, maxillofacial radiology, oral and maxillofacial surgery, pediatric dentistry, oral sciences, periodontology, community dentistry, epidemiology, dental hygiene, education sciences, and restorative dentistry (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The use of a suitable temporary storage solution or technique for an avulsed tooth should not delay efforts at replantation, but it may aid in the survival of the tooth before receiving professional help. While recent systematic reviews attempted to identify the most recommended media for storing an avulsed tooth based on descriptive analysis of (cultured) PDL cell viability, 10,21,22 this systematic review is the first to quantitatively report on the comparisons between various storage media and techniques available to laypeople and the currently recommended transport solutions: milk and saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews have focused mainly on the viability of cultured PDL cells and found that of the media which are available to laypeople, HBSS, 21–23 milk, 21,22 propolis, 10,21,22 coconut water, 10,21,22 and aloe vera gel, 10,21 were most effective in preserving the cell viability. In this systematic review, the limited evidence available favors storing an avulsed tooth in HBSS or propolis compared with milk prior to replantation but there was conflicting evidence regarding the potential of coconut water and aloe vera gel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations